2012
DOI: 10.1177/030006051204000639
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Detection of Influenza A and B Viruses by Different Methods

Abstract: The multiplex PCR test and the rapid antigen test are both effective in the detection of influenza A and B viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Contrary to other studies where the gel-based assay was less sensitive than the real-time RT-PCR assay and the sensitivity and specificity of the real-time RT-PCR relative to the gel-based RT-PCR was 100% and 95%, respectively [17,24]. The diagnostic specificity of conventional RT-PCR is 88.89%, confirmed by other studies as well [25]. The two discordant samples were positive by the realtime RT-PCR and negative by the RT-PCR, a discrepancy most likely due to the higher sensitivity of the real-time RT-PCR assay when compared to the gel-based RT-PCR.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Contrary to other studies where the gel-based assay was less sensitive than the real-time RT-PCR assay and the sensitivity and specificity of the real-time RT-PCR relative to the gel-based RT-PCR was 100% and 95%, respectively [17,24]. The diagnostic specificity of conventional RT-PCR is 88.89%, confirmed by other studies as well [25]. The two discordant samples were positive by the realtime RT-PCR and negative by the RT-PCR, a discrepancy most likely due to the higher sensitivity of the real-time RT-PCR assay when compared to the gel-based RT-PCR.…”
Section: Discussionsupporting
confidence: 54%
“…The positive predictive value (the proportion of patients with positive results who have influenza) of an RT-PCR is lowest when influenza activity is low. The negative predictive value (the proportion of patients with negative results who do not have influenza) of an RT-PCR is highest when influenza activity is low [25].…”
Section: Discussionmentioning
confidence: 99%
“…While the findings of the current study suggest FLU-PRO scores are reliable, valid, and responsive in this expanded target population, the study had several limitations. First, although patients were tested for influenza using RIDTs, the sensitivity and sensitivity of these tests for detecting influenza A or B can vary, and can differ pending the strain of influenza circulating during any given year [ 15 , 16 ]. Thus, it is likely that some ILI patients in this study were infected with influenza A or B.…”
Section: Discussionmentioning
confidence: 99%
“…According to the package insert, the sensitivity of the EIA utilized in this study was 77% for influenza A but only 69% for influenza B in clinical trials when the sample source was throat swab [6]. Additionally, Ozdemir et al observed that the sensitivity of PCR for detecting influenza B in clinical specimens was roughly half that for detecting influenza A when using shell vial culture as the gold standard: 40% and 77.4%, respectively [15]. The observed higher sensitivity of viral culture in diagnosing those with influenza A (H1N1)pdm09 versus (H1N1) and (H3N2) is likely reflective of the fact that BMTs accounted for a majority of cases of the former.…”
Section: Discussionmentioning
confidence: 99%